PENGARUH DIVIDEND POLICY, FIRM SIZE, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN INDEKS LQ45 PERIODE 2019-2024 - Muhammad Fitra Faizin Sahal; Vidiyanna Rizal Putri (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to analyze the effect of dividend policy, firm size, and leverage on firm value in companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Firm value in this study is measured using the Price to Book Value (PBV) ratio, while dividend policy is proxied by the Dividend Payout Ratio (DPR), firm size by Ln Total Assets, and leverage by the Debt to Equity Ratio (DER). The research method used is a quantitative approach with a causality research type. Sampling was carried out using a purposive sampling method on companies that have consistently been included in the LQ45 index for six consecutive years and have complete financial report data. Data were analyzed using panel data regression through EViews 12 software, with classical assumption testing and hypothesis testing. The results show that dividend policy has no effect on firm value. Firm size and leverage were found to have a negative effect on firm value. These findings indicate that large dividend distributions do not always increase company value, large company size and high leverage levels do not necessarily reflect good performance in the eyes of investors.